The early Latin verb system : archaic forms in Plautus, Terence, and beyond - Melo, Wolfgang David Cirilo de, 1976- (Oxford classical monographs., 2007)
The first comprehensive treatment of Latin extra-paradigmatic verb forms, that is, verb forms which cannot easily be assigned to any particular tense in the Latin verbal system. - ;This is the first comprehensive treatment of Latin extra-paradigmatic verb forms, that is, verb forms which cannot easily be assigned to any particular tense in the Latin verbal system. In order to see what functions such forms fulfil, one has to compare their usage to that of the regular verb forms. In Part 1, Wolfgang de Melo outlines the usage of regular verb forms, which, surprisingly, has not always been descri.